What Predicts the Mood of Athletes Involved in Preparations for Tokyo 2020/2021 Olympic Games During the Covid -- 19 Pandemic? The Role of Sense of Coherence, Hope for Success and Coping Strategies. - Szczypińska, Marta; Samełko, Aleksandra; Guszkowska, Monika (Journal of Sports Science & Medicine, 2021)
The aim of the study was to identify coherence, hope for success and coping strategies as predictors of mood among this year's Olympians in the context of coronavirus events. The relationships between the above variables and the mood of athletes were analysed. The study group consisted of 57 athletes -- women (29) and men (28) between 18 and 39 years of age -- representing various sports disciplines who were preparing for the Tokyo Olympics. The research was conducted in the period of April 7-28, 2020 during the first threat of COVID-19 pandemic, following the decision to move the Summer Olympics to the year 2021. It was time of the greatest national restrictions and information about the postponement of the games had been received. As a result of the step regression analysis, three predictors of vigour were established: sense of meaningfulness, coping with stress through positive reframing, and not using the self-blaming strategy. A positive predictor of anger was the use of substances. Confusion was predicted based on the frequency of behavioral disengagement. Behavioral disengagement predicted the severity of depression. Predictors of fatigue were the sense of meaningfulness, and the strategies of positive reframing and self-blaming. The results obtained emphasize the importance of positive reframing as a factor contributing to maintaining a positive mood state. In contrast, behavioral disengagement and self-blaming were strategies that lowered the mood of elite athletes. The results confirm the importance of factors included in the salutogenic model (sense of coherence, coping strategies) as predictors of athletes' mood during a pandemic.